ABX464 (obefazimod) for patients with COVID-19 at risk for severe disease: miR-AGE, a randomized, double-blind placebo-controlled trial - Pedro Giavina-Bianchi, MD, PhD; Eric Cua, MD; Karine Risso, MD; Véronique Mondain, MD; Anaïs Vissian, MSc; Cécile Joie, MSc; Philippe Pouletty, MD; Paul Gineste, PharmD; Hartmut J. Ehrlich, MD, PhD; Jorge Kalil, MD, PhD (Journal of Allergy and Clinical Immunology: Global, 2023)
Background: ABX464 (obefazimod) is a small molecule that upregulates a single microRNA (miR-124) in immune cells and reduces the production of various inflammatory cytokines and chemokines. Objective: We assessed the efficacy and safety of the standard of care (SoC) plus oral obefazimod (SoC plus ABX464), 50 mg once daily, versus the SoC plus placebo for prevention of severe acute respiratory syndrome in patients with coronavirus disease 2019 (COVID-19) who are at risk for severe disease. Methods: Eligible patients for this phase 2/3 double-blind, placebo-controlled miR-AGE study were randomized (2:1) into 2 groups: SoC-ABX464 (n = 339) and SoC-placebo (n = 170). The primary end point was the percentage of patients who did not require use of high-flow oxygen or invasive or noninvasive mechanical ventilation within 28 days. The safety analyses included patients who had been randomly assigned and had received at least 1 dose of the study treatment. Results: At the time of the interim analysis, obefazimod showed no benefit over placebo when added to the SoC; the study enrollment was stopped for futility. The evaluation of the safety of obefazimod in 505 patients showed significantly more treatment-emergent adverse events in the SoC-ABX464 group than in the SoC-placebo group (P = .007). Frequently reported AEs in the SoC-ABX464 group included headache (14.6%), abdominal pain (9.6%), diarrhea (9.0%), back pain (6.9%), and nausea (6.0%). No treatment-related changes in laboratory parameters were reported. Conclusion: For patients who have severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and are at risk for severe COVID-19, obefazimod, 50 mg, provided no benefit over placebo when added to the SoC, although it did have a good safety profile (comparable to that reported in many therapeutic areas).